APPRAISAL IN THE JAKARTA POST ARTICLES ON NATIONAL EXAMINATION (Universitas Negeri Semarang, 2014)
This study is about appraisals which were used to evaluate the interpersonal meanings found in the article texts published in The Jakarta Post newspaper.It is Â aimed to answer mainly questions: what appraisals are used in the article texts? andÂ what is the ideology of the of the article texts? The research design of this study is qualitative descriptive. Qualitative method is intended to unmask the text under analysis, while descriptive method is meant to describe the realization interpersonal meanings by using appraisal system as introduced by Martin and Rose (2003).The analysis was based on the system of appraisals which devided into three sub-systems: systems of affect,appreciation, and judgement.The analysis showed that the writers of the texts applied all of the apprpraisal devices (systems of affect, judgement, appreciation, system of amplification, the source of attitudes system, taxis and logico-semantic relation system) including the addressees of the appraisals, and the ideolgy of the texts. While the results of the analysis based on the appraisals devices indicated that most of the evaluation fell on the negative categories. Moreover, based on the ideological analysis, the writer of the texts seemed to refuse the implementation of national examination as the topic under analysis.